2018
DOI: 10.1016/j.jalz.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Sex, amyloid, and APOE ε4 and risk of cognitive decline in preclinical Alzheimer's disease: Findings from three well‐characterized cohorts

Abstract: Although Aβ did not differ by sex, cognitive decline was greater in females with higher Aβ. Our findings suggest that sex may play a modifying role on risk of Alzheimer's disease-related cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
159
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 187 publications
(182 citation statements)
references
References 60 publications
19
159
4
Order By: Relevance
“…Similarly, we replicated findings from other independent cohorts of the relationship between higher Aβ and increased age [5,6]. Meta‐analyses do not support a relationship between sex and high Aβ [4,31,32], although one observational study reported a female bias [33]. We extend these findings by reporting the magnitude of predictive utility that SCD measurement can provide about the likelihood of Aβ positivity in combination with predominating factors (e.g., age, APOE ).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, we replicated findings from other independent cohorts of the relationship between higher Aβ and increased age [5,6]. Meta‐analyses do not support a relationship between sex and high Aβ [4,31,32], although one observational study reported a female bias [33]. We extend these findings by reporting the magnitude of predictive utility that SCD measurement can provide about the likelihood of Aβ positivity in combination with predominating factors (e.g., age, APOE ).…”
Section: Discussionsupporting
confidence: 82%
“…However, differences in cognitive test batteries across cohorts required substitution with measures assessing the same cognitive process. The PACC has exhibited relative concordance of the baseline and slopes among these cohorts despite differences in measures. The PACC was computed separately in each cohort by averaging the z‐transformed scores for each measure derived from cohort‐specific sample means and standard deviations.…”
Section: Methodsmentioning
confidence: 94%
“…Many studies have evaluated the temporal order in which cognitive tests change in biomarker‐defined cohorts. Memory tests, such as the Free and Cued Selective Reminding Test (FCSRT) and CVLT‐2, are among the most sensitive [26,35]. When we examined the relationship between different CSF markers of neurodegeneration and standardized measures of cognition, we found that ratios of candidate synaptic biomarkers to Tau correlated strongly with sensitive measures from the CVLT that probe memory acquisition and retention or the MDRS that assesses more general cognitive function.…”
Section: Discussionmentioning
confidence: 99%